Indonesia’s Responsibility as a Non-Party to the 1951 Convention and 1967 Protocol on the Status of Refugees in its Protection - Ibrahim Sagio (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Under ordinary circumstances, someone who enters other countries shall be provided with travel documents and required visa as entry permit. On the other hand, if they enter to the territory of another country because of feeling well-founded fear, such as their safety are threatened; and the country of their origin occurs social unrest or war. Therefore, the person may not have complete travel documents and visas. Movement of people who want to enjoy the protection of another country because they feel unsafe in their own country can be filed a request for refugee status. International refugee problem (Refugee) has existed since 1921, the prior international community responded to such events to the preparation of the 1951 Convention and the 1967 Protocol on the Status of Refugee. Nowadays, many countries have ratified them. In both these legal instruments, these contained provisions on international protection standards to international refugees for the states parties. For the countries that are not a party to the Convention and the Protocol, such as the Indonesian state, is not bound to the provisions of these legal instruments. Indonesia as well as other countries that have not ratified, then they have only a moral obligation or humanitarian responsibility. Based on the principle of humanity in the entire country, although they have not yet ratified, there is no a reason to refuse in protecting the refugees.